Kualitas dan Hasil Kacang Tanah pada Lingkungan dengan Perbedaan Ketersediaan Air dan Aplikasi Dolomit - Rahmianna, A. A.; Taufiq, A.; Yusnawan, E. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
The soil moisture availability during the later part of generative growth stage affects pod yield, seed quality, and aflatoxin contamination of groundnut. Pod filling and seed development process are affected by calcium availability in the pod zone. An experiment was conducted with an objective to obtain a conducive condition for groundnut plant growth to obtain high pod yield with sound mature kernels, low Aspergillus flavus infection and low aflatoxin contamination. The experiment was conducted at Joho village, Banjarnegara regency, from June to September 2005. A split plot design was used and nested in two soil moisture conditions, i.e., optimum, where soil moisture was available during the entire groundnut growing period, and suboptimum, where soil moisture was available only during the first 65 days after sowing (DAS. The two main plots were application of 500 kg Dolomite/ha (140 kg/ha CaO) and without Dolomite. The sub-plots were toxigenic A. flavus inoculation at 55 DAS and without A. flavus inoculation. Results of the trial indicated that the groundnut crops grown under an optimum soil moisture condition produced the same pod yield as that grown under the suboptimum moisture condition. Productivity of the groundnut grown under the optimum water availability was 113.7 g dry pods/plant; this was 21.5 g (23.3%) higher than that of the plant grown under the suboptimum soil moisture condition. This result was due more to higher seed yield rather than to bigger seed size and seed/pod weight ratio. Groundnut pod yield per ha however, were not significantly different among treatments. To generate mature and healthy groundnut pods and seeds, optimum soil moisture, especially from pod filling/maturity to harvesting, together with lime application (500 kg Dolomite/ha) need to be applied. Sound mature kernels and free A. flavus infection and low aflatoxin contamination were achieved by application of 500 kg Dolomite/ha, as calcium contained in Dolomite reduced A. flavus infection in the groundnut seeds during maturation, and reduced the number of shriveled seeds.